Acute toxicity bioassays using Daphnia magna Straus (Cladocera, Daphniidae) maintained in a modified culture medium - Núñez, Mónica (2005)
Daphnia magna is a test organism used in ecotoxicological assays of freshwater; however, traditional culture systems for this organism could result expensive, for that the aim of this research was to developed a new economic culture medium. With this purpose, 10 strains of D. magna were isolated, their population development was evaluated by total count of organisms and pregnant females using 3 different culture media: (A) alfalfa juice, (B) solved yeast and (C) a mixture of alfalfa juice plus solved yeast. Successful development of 4 strains was observed in the A medium, but the same strains failed to survive in the B and the C media. The 24h and 48h EC50 average values in acute ecotoxicological assays with potassium dicromate were 0,4045 mg/L ± 0,0389 and 0,1857 mg/L ± 0,0072 respectively. Also, acute ecotoxicological assays with these 4 strains were performed using potassium cyanide, which is a toxic reactive frequently used in mining operations. In this case 24h EC50 value was 1,5388 mg/L ± 0,1146 and 48h EC50 values were 0,6359 mg/L ± 0,0516. 48h EC50 values were lower than the cyanide permissible effluent values established by the Energy and Mining Authority.